Molecular Diversity and Biochemical Content in Two Invasive Alien Species: Looking for Chemical Similarities and Bioactivities - Vega Sánchez, Julia; Catalá, Teresa S.; García-Márquez, Jorge; Speidel, Linn G.; Arijo-Andrade, Salvador; Kunz, Niklas Cornelius; Geisler, Christoph; López-Figueroa, Félix (IOAP-MDPI, 2022)
The biochemical composition, molecular diversity, and two different bioactivities of Asparagopsis armata and Rugulopteryx okamurae (two alien species with different invasive patterns in the southern Iberian Peninsula) were analyzed through spectrophotometric methods and Fourier transform ion cyclotron mass spectroscopy (FT-ICR-MS). A total of 3042 molecular formulas were identified from the different extracts. The dH2O extracts were the most molecularly different. A. armata presented the highest content of nitrogenous compounds (proteins, CHON) and sulphur content, whereas R. okamurae was rich in carbonated compounds (total carbon, lipids, CHO, and CHOP). Antioxidant capacity and phenolic content were higher in R. okamurae than in A. armata. Antimicrobial activity was detected from both species. A. armata showed capacity to inhibit human and fish pathogens (e.g., Staphylococcus aureus or Vibrio anguillarum), whereas R. okamurae only showed inhibition against human bacteria (Staphylococcus aureus and Cutibacterium acnes). In R. okamurae, molecules with a great number of pharmaceutical activities (e.g., anti-inflammatory or antitumoral), antibacterial, biomaterial, and other utilities were found. The main molecules of A. armata had also pharmaceutical applications (e.g., antimalarian, antithrombotic, anti-inflammatory, or antiarthritis). The valorization of these species can help to counteract the environmental effects of the bioinvasions.
Keywords: Polifenoles vegetales; Antioxidant capacity; Asparagopsis armata; Molecular composition; Polyphenols; Rugulopteryx okamurae; Ultrahigh resolution mass spectrometry